Diagnosis and treatment of pleomorphic rhabdomyosarcoma of the uterus: a rare case report and review of the literature. Issue 5 (May 2021) - Li, Zi-Jun; Li, Cheng-Lie; Wang, Wei; Fu, Xiao-Ying; Zhen, Ya-Qin
Pleomorphic rhabdomyosarcomas of the uterus (PRMSu) is a rare malignant tumor of the female genital tract. Accurate diagnosis and effective treatment of PRMSu are important. We report an 81-year-old woman who was diagnosed with PRMSu. She had an extremely unusual presentation of secondary dyspnea because of an extremely large uterus (26.0 cm). Pelvic magnetic resonance imaging showed rare severe enlargement and intrauterine filling with tumor tissue, and she was initially diagnosed with uterine leiomyosarcoma. The patient underwent hysterectomy, as well as bilateral salpingo-oophorectomy and omentectomy, and was finally confirmed as having PRMSu by histopathology combined with immunohistochemistry. We performed a systematic review of the literature between 1982 and 2020 and focused on different treatment strategies and prognosis of PRMSu. A retrospective review of 28 cases was conducted and survival analysis was estimated by using the Kaplan–Meier method. We found that the accuracy of diagnosis of PRMSu completely depends on histopathology and immunohistochemistry because of no special clinical symptoms, no sensitive tumor markers, and no special imaging findings. Although there is no standardized approach for treating this rare disease, the treatment strategy of a surgical operation combined with adjuvant chemotherapy appears to be the best choice.